2011
DOI: 10.1179/174329211x13049558293678
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial redox signaller pyocyanin as an antiplasmodial agent: comparisons with its thioanalog methylene blue

Abstract: The quorum sensor and signalling molecule pyocyanin (PYO) contributes significantly to the pathophysiology of Pseudomonas aeruginosa infections. Comparison to phenothiazine drugs suggests that the antimalarial compound methylene blue (MB) can be regarded as a sulfur analog of PYO. This working hypothesis would explain why the synthetic drug MB behaves as a compound shaped in biological evolution. Here we report on redox-associated biological and biochemical properties of PYO in direct comparison to its synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 63 publications
0
38
0
Order By: Relevance
“…Because research with the Pseudomonas aeruginosa phenazine pyocyanin has shown that phenazines can also modulate host eukaryotic cells, it is to be hoped that these interactions will also be investigated in more detail in the future. The recent structure of a complex with glutathione reductase in a work aimed at understanding the anti-malarial properties of pyocyanin can be regarded as a starting point for such studies [50]. …”
Section: Discussionmentioning
confidence: 99%
“…Because research with the Pseudomonas aeruginosa phenazine pyocyanin has shown that phenazines can also modulate host eukaryotic cells, it is to be hoped that these interactions will also be investigated in more detail in the future. The recent structure of a complex with glutathione reductase in a work aimed at understanding the anti-malarial properties of pyocyanin can be regarded as a starting point for such studies [50]. …”
Section: Discussionmentioning
confidence: 99%
“…The medicinal use of methylene blue dates back to the late 1800s as a treatment for malaria, a urinary analgesic, and in the treatment for cyanide and carbon monoxide poisoning [3][4][5][6]. Methylene blue is currently utilized as a treatment for ifosfamide neurotoxicity [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In stark contrast, there is a dearth of information about biologically catalyzed phenazine reduction. Although pyocyanin and PCA are known to oxidize the electron donors NAD(P)H, dihydrolipoamide, and glutathione in vitro (15,28), it is unknown whether this is relevant in vivo or whether it is enzymatically catalyzed. To address this unknown, previous work in our laboratory attempted to identify phenazine reductases by screening transposon mutants (29,30).…”
mentioning
confidence: 99%